Orthostatic Hypotension and Novel Blood Pressure Associated Gene Variants in Older Adults: Data From the TILDA Study. (10th December 2019) - Laird, Eamon; O'halloran, Aisling M; Fedorowski, Artur; Melander, Olle; Hever, Ann; Sjögren, Marketa; Carey, Daniel; Kenny, Rose Anne
Abstract: Orthostatic hypotension (OH) is associated with increased risk of trauma and cardiovascular events. Recent studies have identified new genetic variants that influence orthostatic blood pressure (BP). The aim of this study was to investigate the associations of candidate gene loci with orthostatic BP responses in older adults. A total of 3, 430 participants aged ≥50 years from The Irish Longitudinal Study on Ageing (TILDA) with BP measures and genetic data from 12 single-nucleotide polymorphism (SNP) linked to BP responses were analyzed. Orthostatic BP responses were recorded at each 10 s interval and were defined as OH (SBP drop ≥20 mmHg or DBP drop ≥10 mmHg) at the time-points 40, 90, and 110 s. We defined sustained OH (SOH) as a drop that exceeded consensus BP thresholds for OH at 40, 90, and 110 s after standing. Logistic regression analyses modeled associations between the candidate SNP alleles and OH. We report no significant associations between OH and measured SNPs after correction for multiple comparisons apart from the SNP rs5068 where proportion of the minor allele was significantly different between cases and controls for SOH 40 ( p = . 002). After adjustment for covariates in a logistic regression, those with the minor G allele (compared to the A allele) had a decreased incidence rate ratio (IRR) for SOH 40 (IRR 0.45, p = . 001, 95% CI 0.29–0.72). Only one SNP linked with increased natriuretic peptide concentrations was associated with OH. These results suggest that genetic variants may have a weak impact on OH but needs verification in other population studies.